A behavioral science/behavioral medicine core curriculum proposal for Japanese undergraduate medical education. Issue 1 (December 2015) - Tsutsumi, Akizumi
Abstract Behavioral science and behavioral medicine have not been systematically taught to Japanese undergraduate medical students. A working group under the auspices of Japanese Society of Behavioral Medicine developed an outcome-oriented curriculum of behavioral science/behavioral medicine through three processes: identifying the curriculum contents, holding a joint symposium with related societies, and defining outcomes and proposing a learning module. The behavioral science/behavioral medicine core curriculum consists of 11 units of lectures and four units of practical study. The working group plans to improve the current core curriculum by devising formative assessment methods so that students can learn and acquire attitude as well as the skills and knowledge necessary for student-centered clinical practice.